Comparisons of abdominal wall reconstruction for ventral hernia repairs, open versus robotic - Barbara Nguyen (Nature Portfolio, 2021)
Abstract The surgical complexities of our current population have pushed the technological limits of healthcare, urging for minimally invasive approaches. For ventral hernias, in particular, robotic assisted laparoscopic repairs have been met with conflict. Cost and longer operative times are among the arguments against robotic surgery, although thorough evaluation of patient outcomes could potentially advocate for use of this tool. We attempted to approach this by retrospectively reviewing our own data. We reviewed charts between September 2016 and February 2017 of patients receiving complex hernia repairs, either a standard open repair (SOR) or robotic-assisted repair (RAR). Data collected included preoperative, perioperative, and postoperative care. Of the 43 patients reviewed, 16 were SOR, versus 27 RAR. Patients were comparable in age, gender, BMI, diabetes as a comorbidity; average hernia defect size was similar between the two groups. Although operative times were longer in the RAR group, estimated blood loss (EBL) was less. Hospital stay was also shorter in the RAR group, at 3.0 ± 1.9 days versus 9.6 ± 8.4 days for the OAR group. Of those requiring critical care management, only one patient had a robotic assisted repair, versus half of the patients who received an open repair. Of the patients who presented to the emergency department within 30 days of surgery, each group had four patients, and two from the OAR group required admission. Our data is consistent with other literature supporting shorter lengths of stays. Although the robotic approach did required a longer operative time, the resulting improved patient outcomes support this technique for complex ventral hernia repairs.